Experimental determination of the activation energies of CH4, SO2 and O2 reactions on Cr2O3/γ-Al2O3 - Hernández Guiance, Sabrina Noemí (2016)
In the present work we experimentally determine the activation energies of CH4,SO2 and O2 reactions on Cr2O3/γ-Al2O3. To our knowledge there is no previous determination of these parameters, so fundamental information is provided to determine the velocity laws of these reactions and understand their kinetic behavior.